2019
DOI: 10.7567/1347-4065/ab124b
|View full text |Cite
|
Sign up to set email alerts
|

Plasma assisted-MBE of GaN and AlN on graphene buffer layers

Abstract: The possibility of using chemical vapor deposition (CVD) graphene as a 2D buffer layer for epitaxial growth of III-nitrides by plasma assisted-MBE on amorphous substrates (SiO 2 prepared by thermal oxidation of Si wafer) was investigated. The comparative study of graphene-coated parts of the wafers and the parts without graphene was carried out by scanning electron microscopy and X-ray diffractometry. It was shown that epitaxial GaN and AlN films with close to 2D surface morphology can be obtained by plasma as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…GaN films are deposited on Si substrates mainly through chemical reactions of the Ga and N sources on the substrate surface by MOCVD [36,37] and MBE [38]. Since the initial fabrication of GaN-based HEMTs on Si using MOCVD and MBE [39,40], fabrication techniques have undergone rapid development, as indicated by µ N growing from approximately 900 cm 2 V −1 s −1 to more than 2000 cm 2 V −1 s −1 [41].…”
Section: Gan-based Hemt On Si Substratementioning
confidence: 99%
“…GaN films are deposited on Si substrates mainly through chemical reactions of the Ga and N sources on the substrate surface by MOCVD [36,37] and MBE [38]. Since the initial fabrication of GaN-based HEMTs on Si using MOCVD and MBE [39,40], fabrication techniques have undergone rapid development, as indicated by µ N growing from approximately 900 cm 2 V −1 s −1 to more than 2000 cm 2 V −1 s −1 [41].…”
Section: Gan-based Hemt On Si Substratementioning
confidence: 99%
“…In some recent works, researchers regarded graphene as a suitable 2D buffer, which facilitated the high-quality epitaxy of III-nitrides layers on a silicon substrate via both the MOCVD [13][14][15][16] and MBE techniques [17][18][19]. Graphene has a hexagonal crystal lattice comparable to the (0001) plane of a GaN (AlN) crystal in the wurtzite phase.…”
Section: Introductionmentioning
confidence: 99%
“…5,6) One of them is to use graphene as a crystalline buffer layer for GaN growth. [7][8][9][10][11][12][13][14][15][16][17][18][19] Even though the substrate is amorphous, high-quality GaN films can be grown on the graphene-covered substrates. 8,9,13,15,16,19) Besides, because graphene weakly interacts with the substrate and grown materials, GaN growth on graphene allows us to produce freestanding GaN films by mechanical exfoliation, 7,14) which could contribute to flexible photonics/electronics applications.…”
mentioning
confidence: 99%
“…Using in-situ XRD, the lattice parameters of GaN were precisely measured during growth, and the crystal orientation was determined after growth. Because it has been reported that the AlN buffer layers improve the GaN crystal quality on graphene, 15,16,19) the influence of AlN on GaN growth is also studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation